Recruitment of Prospective Candidate Members of the General Election Supervisory Agency Case Study: Thirteen Districts-Cities South Borneo Province - Dicky Pratama; Dewi Susita; Puji Wahono (MultiTech Publisher, 2024)
Human resource management plays a very important role in organizations, both with public organizations and others, such as the General Election Supervisory Agency (Bawaslu). Therefore, the recruitment process for prospective Bawaslu members emphasizes various components, namely track records such as performance records or actual achievements of independence, integrity and leadership spirit. This research aims to 1). To find out and analyze the process of determining Bawaslu Commissioner members in the Regency-City Bawaslu recruitment for South Borneo Province. 2). To find out the ideal model for Regency-City Bawaslu recruitment. Data collection techniques use observation, interviews and documentation. This type of research is field research, while the method used is a qualitative descriptive method. Then to carry out data processing and analysis using the NVivo software program. The results of research regarding the recruitment process for prospective members of the Regency-City Bawaslu of South Borneo Province in 2023 were carried out well and in accordance with the regulations. However, the process still contains obstacles, such as at the registration stage the number of registrants is less than what is needed, especially female registrants, at the administration stage there are a lot of costs incurred to complete the requirements, the CAT system creates problems that are considered to make carrying out recruitment difficult for the affirmation policy, health tests are considered useless because at this stage a second health test is carried out, problems occur at the fit and proper test stage related to several postponements of the announcement time which do not match the timeline, the organizational hierarchy at the fit and proper test stage is not ideal, and the need for consideration and more serious efforts related to supporting women's representation as Bawaslu members.